Women in community corrections in New York City: HIV infection and risks. (February 2017) - El-Bassel, Nabila; Marotta, Phillip L; Shaw, Stacey A; Chang, Mingway; Ma, Xin; Goddard-Eckrich, Dawn; Hunt, Tim; Johnson, Karen; Goodwin, Sharun; Almonte, Maria; Gilbert, Louisa
Although the incidence of HIV among women on probation, parole and alternatives to incarceration programs is significant to public health, drivers of this concentrated epidemic among women under community corrections remain understudied. This study examined prevalence of HIV and sexually transmitted infections and the associations between substance use, socio-demographic factors and the prevalence of biologically-confirmed HIV and other sexually transmitted infections among a sample of 337 substance-using women recruited from community correction sites in New York City. Prevalence of HIV was 13% and sexually transmitted infections was 26% ( Chlamydia, trachomatis and Neisseria gonorrhea). After adjusting for covariates, HIV-positive women were 1.42 times more likely to use crack/cocaine than HIV-negative women (95% CI = 1.05–1.92). HIV-positive women were 25% less likely than HIV-negative women to report any unprotected vaginal and anal sex with their main partner (95% CI = 0.57–0.99). They were 70% less likely than HIV-negative women to report unprotected vaginal sex with a non-paying casual partner (95% CI = 0.1–0.9) and 22% less likely to report unprotected vaginal sex across all partners (95% CI = 0.61–0.99). Community corrections settings may be optimal venues to launch HIV/sexually transmitted infections prevention that have potential to reach and engage an ever-growing number of substance-using women.